Cloud Native Java with Kubernetes. (LiveLessons (Boston, Massachusetts), 2022)
10.5+ Hours of Video Instruction Description Work takes time to flow through an organization and ultimately be deployed to production, where it captures value. It's critical to reduce time-to-production. Software is a competitive advantage for many organizations and industries. Organizations break their larger software ambitions into smaller, independently deployable, feature-centric batches of work--microservices. To reduce the round trip between stations of work, organizations collapse or consolidate as much of them as possible and automate the rest; developers and operations beget "devops"; and cloud-based services and platforms (like Cloud Foundry) automate operations work and break down the need for ITIL tickets and change management boards. But velocity, for velocity's sake, is dangerous. Microservices invite architectural complexity that few organizations are prepared to address. In Cloud Native Java with Kubernetes LiveLessons, 2nd Edition, we look at how high-performance organizations are addressing the requirements of distribution with Spring Boot, Spring Cloud, and Kubernetes to be more resilient, reliable, robust, and scalable. Related Titles Microservices with Spring Boot LiveLessons, 2nd Edition by Josh Long and Philip Webb Reactive Spring Boot LiveLessons, 2nd Edition by Josh Long About the Instructor Josh Long (@starbuxman) is the spring developer advocate at Pivotal. Josh is a Java Champion, the author of five books (including Cloud Native Java: Designing Resilient Systems with Spring Boot, Spring Cloud, and Cloud Foundry) and six best-selling video trainings (including Building Microservices with Spring Boot LiveLessons with Phil Webb), and is an open source contributor (Spring Boot, Spring Integration, Spring Cloud, Activiti, and Vaadin). Skill Level Intermediate What You Will Learn How high-performance organizations are addressing the requirements of distribution with Spring Boot, Spring Cloud, and Kubernetes The need for cloud native Foundational first steps in Java, Kotlin, Spring Boot, Reactive Programming, Containers, and Kubernetes How to turn applications into docker images to package for production How to build native images with Spring Native Build observable services Implement continuous integration and continuous delivery Build applications into the production cloud with Azure Spring Cloud Build distributed systems including configuration, service registration, and discovery and RSocket and edge services Extend the platform by building on top of Kubernetes to enhance the platform using Spring Who Should Take This Course Java developers interested in deploying applications to the cloud using Spring Cloud Enterprise developers who need to quickly build new applications that are scalable, portable, resilient, and easily updated Course Requirements Experience with Java EE or Spring and a basic knowledge of distributed computing, cloud-based services, Agile methods, and microservice architectures. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.